“It’s What We Do Every Day”: Recruiting Tomorrow’s Robotic Warriors - Howley, Kevin (Journal of Marketing Development and Competitiveness, 2020)
Employing content and discourse analysis, this paper examines the discursive strategies and practices behind a United States Air Force (USAF) recruitment advertisement featuring a new generation of hi-tech weapon systems: Remotely Piloted Aircraft (RPAs), better known as drones. I locate this discussion in relation to critical scholarship on the military-industrial-media-entertainment complex and its implications for naturalizing a state of perpetual war. Following this, I chart the evolution of USAF commercials from the Vietnam era to the present. In this way, I highlight continuity and change in the visual rhetoric and discursive strategies deployed in these campaigns. Next, I perform a close reading of the drone spot with a discrete focus on the rhetoric of the technological sublime operating throughout. Doing so, I contend that the advertisement articulates the admixture of awe and fear, apprehension and wonder that has come to shape public understanding of drone technology. The paper concludes with some thoughts on the cultural work taken up by this commercial: the recruitment of next generation soldiers and the normalization of remote control warfare.